Quality of fresh and cryopreserved bovine sperm is reduced by BPA and BPF exposure - Ola S Davis; Vivien B Truong; Katie D Hickey; Laura A Favetta (Bioscientifica, 2023)
Bisphenol A (BPA) is an endocrine-disrupting compound, used as the key monomer of polycarbonate plastics and epoxy resins. BPA has been detected in both humans and farm animals and has been correlated with decreased sperm counts and motility. BPS and BPF are structural analogs of BPA and are increasingly being used in manufacturing as BPA substitutes. In this study, we aim to assess the direct outcomes of BPA, bisphenol S (BPS), and bisphenol F (BPF) exposure on bovine sperm parameters in vitro to elucidate how they affect sperm quality and fertilization potential, and to assess whether BPS and/or BPF are less harmful than BPA. Sperm from three or more bulls was obtained from either fresh samples or cryopreserved straws and exposed to 0.05 mg/mL of BPA, BPS, and BPF in vitro. After 4 h incubation, motility, capacitation, apoptosis/necrosis, and mitochondrial membrane potential levels were measured by computer-assisted sperm analysis or computational flow cytometry. Results showed that BPA exposure significantly reduced both fresh and cryopreserved sperm motility, capacitation, viability and mitochondrial membrane potential levels. Furthermore, BPF significantly decreased motility, capacitation and mitochondrial membrane potential in cryopreserved sperm only. BPS did not have any significant effects on any of the parameters measured. Our results suggest that BPA is the most harmful to sperm, while BPF is toxic under certain conditions, and BPS seems to be the least detrimental. Overall, this study provides an understanding of how the ubiquitous environmental chemicals, bisphenols, may impact male fertility even after ejaculation.